ZAKAT SEBAGAI ASPEK TABARU DAN PENGUNGKAPAN ISLAMIC SOCIAL REPORTING TERHADAP KINERJA KEUANGAN - Aris Kurniawan; Suliyanto Suliyanto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2013)
Zakat is the 3rd Islam principle from 5 o f them after shalat, zakat is the important maaliyahijtima’iyyah worship whether if we look from the Islam knowledge or from the social aspect for the society welfare. Zakat can be described as a blessing, growth and development. Beside it is compulsory for individual, it is also compulsory for the company. For company, zakat is the tabaru (social) aspect which can help the parties that need help and it also can increase the development o f the company itself. Company zakat are counted based on the general requirements or based on accountancy principle in PSAK No. 109 about the accountancy o f zakat and infaq/sedekah which is legalized on May 2008 by DSAK and IAI where the company’s zakat will be counted 2,5% from the profit after tax. The expression o f Corporate Social Responsibility) in Indonesia is one o f issues which is up to date to be discussed, whether for the conventional or Islamic company. In Islamic company (Syariah Bank) the expression o f CSR is measured by using different index with the expression o f conventional company index. The expression o f CSR in syariah bank is not using CSDI (Corporate Social Disclosure Index) anymore, but by using ISR (Islamic Social Reporting) index which consist o f 6 indicators, they are infestation and finance, organization management, product and service, human resource, social and environment. The development o f the company as the dependent variable in this research was combined with three rentabilitasratios; they are Return On Asset (ROA), Return On Investment (ROI), and Return On Equity (ROE) variable.